SLC7A11 is a potential therapeutic target and prognostic biomarker correlated with immune cell infiltration in cervical cancer - Mutangala Muloye Guy; Tingting Bian; Longyun Sun; Yiping Hao; Xinlin Jiao; Wenjing Zhang; Teng Zhang; Baoxia Cui (Discover Oncology)
Abstract Background SLC7A11 is importantly in both ferroptosis and disulfidptosis which participated in human development and homeostasis. By utilizing bioinformatics and in vitro validation, we explored SLC7A11's role in cervical cancer. Methods From the TCGA database, we analyzed SLC7A11 expression profiles and validated its promoting role in cervical cancer by in vitro. Patients were divided into two subgroups according to SLC7A11 expression levels, and differentially expressed genes (DEGs) were identified between these groups. Then SLC7A11's mechanism was then clarified by function enrichment analysis. The association between SLC7A11 and the immune microenvironment was investigated. Finally, we explore potential drugs by oncoPredict. Results Our findings suggest that SLC7A11 could serve as a valuable prognostic biomarker in cervical cancer. Besides, SLC7A11 was positively regulated cervical cancer cells’ proliferation, migration and invasion. We identified 113 DEGs between two subgroups. Functional enrichment analysis revealed that these DEGs are linked to immune-related pathways. The SLC7A11 high expression group showed greater enrichment of resting NK cells, neutrophils, M0 macrophages, and activated mast cells, whereas the SLC7A11 low expression group had higher levels of resting dendritic cells, resting mast cells, and follicular helper T cells. Besides, there were higher TMB scores in patients with high SLC7A11 expression. Finally, we explore 37 kinds of drugs may improve prognosis. Conclusion SLC7A11, correlated with immune pathway, is a risk factor affecting the prognosis of cervical cancer. We also explore 37 kinds of drugs that may benefit cervical cancer patients.